2023
DOI: 10.1002/ueg2.12472
|View full text |Cite
|
Sign up to set email alerts
|

Toward a more precise prognostic stratification in acute decompensation of cirrhosis: The Padua model 2.0

Alberto Zanetto,
Filippo Pelizzaro,
Monica Maria Mion
et al.

Abstract: BackgroundThe clinical course of acutely decompensated cirrhosis (AD) is heterogeneous. Presepsin (PSP) is a plasmatic biomarker that reflects Toll‐like receptor activity and systemic inflammation. We conducted a prospective study to: (1) measure PSP in AD and (2) assess whether PSP in AD can predict the development of acute‐on‐chronic liver failure (ACLF).MethodsPatients with AD were prospectively recruited at admission and underwent determination of PSP. In study part 1, we compared PSP in AD versus controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…introduced the Padua model 2.0 that identifies patients with AD at a high risk of developing ACLF. 4 This expands on the authors' previous work on the original Padua model, which combined C‐reactive protein (CRP), Chronic Liver Failure Consortium AD score (CLIF‐C AD) and Child Pugh score to predict risk of ACLF in patients with AD, and this model could more accurately predict ACLF development than Model for End‐Stage Liver Disease (MELD), CLIF‐C AD or Child Pugh scores alone. 5 The Padua model 2.0 differs in that CRP is replaced by presepsin (PSP), a soluble fragment of CD14, as the authors found that high levels of PSP characterised patients with AD.…”
mentioning
confidence: 73%
“…introduced the Padua model 2.0 that identifies patients with AD at a high risk of developing ACLF. 4 This expands on the authors' previous work on the original Padua model, which combined C‐reactive protein (CRP), Chronic Liver Failure Consortium AD score (CLIF‐C AD) and Child Pugh score to predict risk of ACLF in patients with AD, and this model could more accurately predict ACLF development than Model for End‐Stage Liver Disease (MELD), CLIF‐C AD or Child Pugh scores alone. 5 The Padua model 2.0 differs in that CRP is replaced by presepsin (PSP), a soluble fragment of CD14, as the authors found that high levels of PSP characterised patients with AD.…”
mentioning
confidence: 73%
“…In this version, CRP was substituted with Presepsin (PSP), a soluble fragment of CD14, expressed by monocytes and macrophages, released during the inflammatory response. PSP demonstrated a stronger correlation with the risk of ACLF development compared with CRP 42 . The improved specificity of PAMPs‐related inflammation is believed to account for the greater performance of Padua 2.0 compared to the Padua model.…”
Section: Clinical Implicationmentioning
confidence: 95%
“…PSP demonstrated a stronger correlation with the risk of ACLF development compared with CRP. 42 The improved specificity of PAMPs‐related inflammation is believed to account for the greater performance of Padua 2.0 compared to the Padua model. If further confirmed, the Padua and Padua 2.0 models could serve as important tools for identifying at‐risk patients who require urgent evaluation for LT and for targeting a population suitable for the development of disease‐modifying drugs.…”
Section: Clinical Implicationmentioning
confidence: 99%
“…8 The release of EVs in decompensated cirrhosis is due to systemic inflammation, chronic liver injury and complications of cirrhosis such as acute kidney injury (AKI). 9,10 Since these events are responsible for hepatic decompensation and/or development of acute-on-chronic liver failure (ACLF), [11][12][13] a recent hypothesis suggests that the determination of plasmatic EVs, particularly the ones derived from hepatocytes, 10,14 could improve prognostic stratification. [14][15][16][17] Bacterial infections are common complications in decompensated cirrhosis, occurring in 30%-40% of hospitalized patients.…”
Section: Backg Round and Aimsmentioning
confidence: 99%